ANALISIS SISTEM AGRIBISNIS USAHA TERNAK KAMBING SABURAI PADA KOPERASI PRODUSEN PETERNAK (KPP) SABURAI MANDIRI DI KECAMATAN GISTING KABUPATEN TANGGAMUS - Panji Hirawan; Dyah Aring Hepiana Lestari; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This research aims were to determine the procurement system saburai goat livestock business production facilities, saburai goat livestock business income, saburai goat production cost, saburai goat marketing channel, saburai goat agribusiness system supporting services and the role of Saburai Mandiri Producer Livestock Cooperative (KPP) in the saburai goat agribusiness system.  The research was taken a case study at KPP Saburai Mandiri located in Gisting Sub-District Tanggamus District.  The procurement of saburai goat livestock business production facilities has been right with an accuracy level of 83,96 percent.  Saburai goat livestock business average income was Rp22.563.979,21 per year.  Saburai goat production cost was Rp31.248,68 per kg.  Saburai goat marketing channel was divided into two types product which each has four marketing channels.  Saburai goat agribusiness system supporting services were financial institutions (banks), extension agencies, government policies, farmer/livestock groups, transportation facilities, information and communication technology and markets.  The role of KPP Saburai Mandiri in saburai goat livestock agribusiness system was already good enough. Key words: Agribusiness, cooperative, livestock business, saburai goat.